Lista taxonómica preliminar del fitoplancton del Río Colorado en Villa Vieja, (dpto. Puelén, La Pampa, Argentina) - Galea, María J. (2012)
This work presents preliminary taxonomic information of the phytoplankton community of the Colorado river, the natural boundary between the provinces of La Pampa and Río Negro. With the objective to know and categorize the algal communities of phytoplankton, samples were collected in Villa Vieja, on the left bank. The study area is located at 38º 14’ 55’’ lat. S; 67° 11’ 49’’ long. W at 232 msnm, downstream of Embalse Casa de Piedra dam. The results correspond to samples taken in February 2010, the period of maximum flow. The samples were collected with plankton net of 20 microns aperture observed in vivo and then fixed in formalin (4%). For studies of diatoms aliquots of the samples and subsequent treatment for the removal of organic matter and making diatom preparations. The physicochemical and environmental were recorded in situ by using portable sensors and subsequent laboratory techniques. Of all taxa identified to the present functional groups recorded were: 32.7% Bacillariophyceae, Chlorophyceae 44.3%, Cyanophyceae 11.5% and 11.5% other algae remaining partners, including Euglenophyceae.